Case Report: A Novel CACNA1S Mutation Associated With Hypokalemic Periodic Paralysis in a Chinese Family - Jin, Jie-Yuan; Guo, Bing-Bing; Dong, Yi; Sheng, Yue; Fan, Liang-Liang; Zhang, Li-Bing (Frontiers in Genetics, 2021)
Hypokalemic periodic paralysis (HypoPP) is a rare autosomal dominant disorder characterized by episodic flaccid paralysis with concomitant hypokalemia. More than half patients were associated with mutations in CACNA1S that encodes the alpha-1-subunit of the skeletal muscle L-type voltage-dependent calcium channel. Mutations in CACNA1S may alter the structure of CACNA1S and affect the functions of calcium channels, which damages Ca2+-mediated excitation-contraction coupling. In this research, we identified and described a Chinese HypoPP patient with a novel frameshift mutation in CACNA1S (NM_000069.2: c.1364delA [p.Asn455fs]) by targeted sequencing. This study would expand the spectrum of CACNA1S mutations, further our understanding of HypoPP, and provided a new perspective for selecting effective treatments.